Meta-analysis of cardiomyopathy-associated variants in troponin genes identifies loci and intragenic hot spots that are associated with worse clinical outcomes. (May 2020) - Tadros, Hanna J.; Life, Chelsea S.; Garcia, Gustavo; Pirozzi, Elisa; Jones, Edward G.; Datta, Susmita; Parvatiyar, Michelle S.; Chase, P. Bryant; Allen, Hugh D.; Kim, Jeffrey J.; Pinto, Jose R.; Landstrom, Andrew P.
Abstract: Introduction: Troponin ( TNN)- encoded cardiac troponins (Tn) are critical for sensing calcium and triggering myofilament contraction. TNN variants are associated with development of cardiomyopathy; however, recent advances in genetic analysis have identified rare population variants. It is unclear how certain variants are associated with disease while others are tolerated. Objective: To compare probands with TNNT2, TNNI3, and TNNC1 variants and utilize high-resolution variant comparison mapping of pathologic and rare population variants to identify loci associated with disease pathogenesis. Methods: Cardiomyopathy-associated TNN variants were identified in the literature and topology mapping conducted. Clinical features were compiled and compared. Rare population variants were obtained from the gnomAD database. Signal-to-noise (S:N) normalized pathologic variant frequency against population variant frequency. Abstract review of clinical phenotypes was applied to "significant" hot spots. Results: Probands were compiled ( N = 70 studies, 224 probands) as were rare variants ( N = 125, 748 exomes; 15, 708 genomes, MAF <0.001). TNNC1 -positive probands demonstrated the youngest age of presentation (20.0 years; P = .016 vs TNNT2 ; P = .004 vs TNNI3 ) and the highest death, transplant, or ventricular fibrillation events ( P = .093 vs TNNT2 ; P = .024 vs TNNI3 ; Kaplan Meir: P = .025). S:N analysis yielded hot spots of diagnostic significance within the tropomyosin-binding domains, α-helix 1, and the N-Terminus in TNNT2 with increased sudden cardiac death and ventricular fibrillation ( P = .004). The inhibitory region and C-terminal region in TNNI3 exhibited increased restrictive cardiomyopathy ( P =.008). HCM and RCM models tended to have increased calcium sensitivity and DCM decreased sensitivity ( P < .001). DCM and HCM studies typically showed no differences in Hill coefficient which was decreased in RCM models ( P < .001). CM models typically demonstrated no changes to Fmax ( P = .239). Conclusion: TNNC1 -positive probands had younger ages of diagnosis and poorer clinical outcomes. Mapping of TNN variants identified locations in TNNT2 and TNNI3 associated with heightened pathogenicity, RCM diagnosis, and increased risk of sudden death. Graphical abstract: Unlabelled Image Highlights: It is unclear how certain variants are well tolerated and others pathogenic. TNNC1 -positive probands carried the poorest prognosis compared to TNNT2 and TNNI3 -positive probands. Signal-to-noise mapping of TNN revealed locations in TNNT2 and TNNI3 associated with pathogenicity and poor prognosis. De novo variants, homozygosity, compound heterozygotes, and double heterozygotes have poorer prognosis.